Hubungan Pengetahuan dengan Peran Serta Masyarakat Pada Program Pemberantasan Malaria Di Kecamatan Cipatujah Kabupaten Tasikmalaya - Sugianto Sugianto; Lukman Hakim (Loka Litbang Kesehatan Pangandaran, 2009)
Abstracts. Malaria control program is aimed to prevent of disease transmission and treatment.The successes of malaria control program depend on many factors. One of those factorsis community participation which is initially by awareness. The study which is aimed toasses relationship between knowledge and community participation was conducted in Sindangkertavillage - Cipatujah Sub District - District of Tasikmalaya. This area has been highendemic malaria since malaria program was launched in southern coastal of java island.Data collection was carried out by interview to 270 respondents which was chosen as a sample.The results of this study are 77.4% of sample is good knowledge however 13% lack participation.Base on statically test, there is not significantly relationship between knowledgeand participation. This research suggested that Health District office of Tasikmalaya haveto undertake facilitating and stewardship for improving community participation by localspecific method and involving of key person as well.